PROFESSIONALISM: AS A SOLUTION TO CONTEMPORARY PROBLEMS IN FUNCTIONAL MATHEMATICS EDUCATION IN NIGERIA - F.O, OJO A.A, EGBON; C.A., ALADESAYE (IJRDO -JOURNAL OF MATHEMATICS, 2016)
This paper stresses on categories of mathematics Teachers and controversy overprofessional recognition as regards challenges that confront educationalprofessionals most especially functional issues in Nigeria. Stakeholders of todayand tomorrow should be prepared to effect changes and innovation and promotethe image of mathematics teacher education in Nigeria through professionalism.Standard for practice vis-a-vis the quality and effectiveness of teachers who havecompetencies through specially designed programmes for solving specific task.The characteristics of a professional, the code of conduct, control of entry and therecognition of the occupation of teacher is being zero into. Somerecommendations were made. Professional association like MAN, NMS shouldprovide new teachers and their mentors with external peer support throughmeetings, conference, publication and other resources. The association shouldensure that mathematics teachers education programme should be built aroundprofessional standards provided by accrediting agencies, department of educationand other educational entities. Hence educational authorities should reach aconsensus such that mathematics education must be transformed to meet the needsof an emerging information technology and service –based society.